Irony in storiesy - سروه يونس أحمد الدلي د. (lark, 2020)
Summary The circumstances that the Arab citizen suffered created the art of irony, for the individual has suffered many problems in his society, which is dominated by paradoxes and political and social conflicts, and the accompanying marginalization of the Arab and intellectual self and neglecting the simplest of what serves this absentee personality. This had a special impact on the same neglected and marginalized Arab intellectual, and we can say that irony in Arab literature was the result of the crisis and the reality of contradictions and paradoxes that contradict the hopes of the Arab citizen and even the Arab intellectual in particular. The subject of study in the group of satirical writer